Design, deployment, and cost considerations for DARMA; a low-cost and lightweight FMCW radar - Bruner, Marshall, author; Chandrasekar, V., advisor; Cheney, Margaret, committee member; Gooch, Ryan, committee member (Colorado State University. Libraries, 2022)
The capability of frequency-modulated continuous wave (FMCW) radar to operate in low-power environments has made it a good choice for many mobile systems including automobile radars. While specialized FMCW radars have seen an increase in production recently, there is a lack of general-purpose FMCW radars with the ability to be used in a multitude of applications, especially for volume targets such as precipitation. This thesis presents design considerations for the Dual-polarization phased Array Radar for Measurement of the Atmosphere (DARMA), a low-cost, medium range (km) radar with the versatility to operate mounted on an unmanned aircraft system (UAS) or ground platform. The radar features modular subsystems which allow for easy swapping to support different application requirements as well as upgrades due to rapidly changing technology. Signal processing methods are also introduced, and implemented on COTS systems, to allow for noise mitigation, target detection, and estimation of weather products.
Keywords: radar; FMCW; weather